2023
DOI: 10.2196/40201
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Features, Influencing Factors, and Solutions for COVID-19 Vaccine Misinformation: Systematic Review

Abstract: Background During the COVID-19 pandemic, infodemic spread even more rapidly than the pandemic itself. The COVID-19 vaccine hesitancy has been prevalent worldwide and hindered pandemic exiting strategies. Misinformation around COVID-19 vaccines is a vital contributor to vaccine hesitancy. However, no evidence systematically summarized COVID-19 vaccine misinformation. Objective This review aims to synthesize the global evidence on misinformation related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 143 publications
0
35
0
1
Order By: Relevance
“…For instance, they may have concerns about whether a specific, recently introduced vaccination lowers the risk of infection while still believing that tested vaccines are generally effective. The hesitant attitudes could be explained by right-leaning media coverage of the virus and, thus, different partisan responses regarding vaccines [ 32 , 33 ]. During the start of the pandemic, denial and misinformation about the coronavirus erupted on right-leaning media sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, they may have concerns about whether a specific, recently introduced vaccination lowers the risk of infection while still believing that tested vaccines are generally effective. The hesitant attitudes could be explained by right-leaning media coverage of the virus and, thus, different partisan responses regarding vaccines [ 32 , 33 ]. During the start of the pandemic, denial and misinformation about the coronavirus erupted on right-leaning media sources.…”
Section: Discussionmentioning
confidence: 99%
“…Political affiliation has also been shown to play a significant role in vaccine decision making. This relationship may be due to shifts in the social norms regarding vaccines among right-wing communities and news media [ 32 , 33 ]. A KFF survey showed that political affiliation was a stronger predictor at the start of the pandemic in terms of mask wearing, social distancing, and receiving vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some associated factors might not be reported, because the included studies did not explore them. For example, vaccination policy and smoking habits were determined to be associated with influenza vaccination willingness [53,54]; trust in the government and information exposure were associated with the COVID-19 vaccine [28,55]. These could be explored in future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Unwillingness to vaccine has been associated with greater psychiatric symptoms in patients with schizophrenia: symptomatic patients with schizophrenia frequently are suspicious of the Government for wanting to vaccinate people and develop paranoid delusions around the vaccination itself and the process [55][56][57]. However, this suspicion was not limited to patients with psychotic disorders and younger age, lower education and economic status, right-wing and conservative ideology have been associated with increased belief in misinformation [58]. COVID-19 vaccination is associated with slight deterioration of the schizophrenia symptoms of elderly hospitalized patients [55].…”
Section: Vaccination Policies Unwillingness To Vaccine and Rates Of V...mentioning
confidence: 99%